Dari Passion ke Profesi: Merancang Masa Depan dengan Bijak - Hairlia, Kayla Najla; ‘Ula, Elviana Rohmah Rosyidatul; Azizah, Taqiyyatul; Sarifah, Lailatus; Tipa, Intan Sofia (Lembaga Yasin AlSys, 2025)
Career guidance is one of the important aspects in the world of education and self-development that aims to help individuals understand their potential, interests, and talents in order to plan and achieve appropriate career goals. The type of research is a qualitative approach with a case study method. The findings of this study discuss 1) Definition of career guidance, 2) Purpose of career guidance, 3) Benefits of career guidance, 4) Types of basic services in career guidance, 5) Career guidance service process, 6) Importance of self-development in career services, 7) Career guidance theory, 8) Challenges and obstacles, 9) The role of technology in career services, and 10) Examples of career services. This study aims to understand social, cultural, or human behavioral phenomena in depth that focus on the meaning, experience, and perspective of individuals or groups and can use descriptive data in the form of written or spoken language and then prioritize the depth of data, not the quantity of data.